Maintenance strategy selection and its impact in maintenance function: A conceptual framework. Issue 12 (7th December 2015) - Velmurugan, R S; Dhingra, Tarun
Abstract : Purpose: – This paper aims to synthesize and categorize the published literatures related to maintenance strategies formulation, selection and implementation in various industries. The purpose of this paper is to develop a conceptual framework based on literature review for formulation of maintenance strategies, selection and the implementation of selected strategies. Further, to study on impact of maintenance strategies implementation in maintenance function. Design/methodology/approach: – A literature review has been carried out to identify the existing frameworks related to maintenance strategies formulation, selection of maintenance strategy and implementation of maintenance strategy in the industry. Literature support for all the conceptual constructs referred in the framework has been discussed to establish a logical sequence. Findings: – A conceptual framework for maintenance strategies formulation, selection and implementation and its impact in maintenance function has been developed. Further, constructs and sub-constructs which form the basis for maintenance strategies formulation, selection and implementation have been identified from the literatures. In addition, propositions have also been formulated to support the conceptual framework and these propositions provide the logical relationship among the maintenance strategies formulation, selection among the formulated strategies and the implementation of these strategies. Research limitations/implications: – The conceptual framework developed in this paper for maintenance strategy formulation and selection is yet to be empirically tested. The proposed framework can be tested in various industries. Practical implications: – Literature study on maintenance strategy formulation and selection has so far been very limited. Maintenance strategy selection is a critical decision-making problem for the maintenance managers working in the process plant, manufacturing companies, etc. The conceptual framework proposed in this paper will help maintenance managers to asses, formulate, select suitable maintenance strategy and implement for their organization. Originality/value: – The paper provides comprehensive study on maintenance strategy problem which will be useful to researchers, maintenance managers and other professionals in various industries such as process industry, manufacturing industry, etc., to understand maintenance strategy selection problem and implementation of maintenance strategy.